PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA TRANSPORTASI ONLINE DI LAMONGAN - Sukahar; Nisaul Ullum; Akhmad Misbakhul Khoir; Yusuf Darmawan; Muad (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
This study aims to determine the influence of promotion and service quality on the decision to purchase online transportation services in Lamongan. The type of research used in this study is quantitative research. The population in this study is consumers who use services from Grab and Cak Ed Delivery in Lamongan with a sample of 75 respondents. Sampling is carried out by non-probability sampling method using purposive sampling. The data collection technique used in this study was by using the questionnaire method. Data analyzed using SPSS 26.0